1982
DOI: 10.1080/15287398209530180
|View full text |Cite
|
Sign up to set email alerts
|

Acute dermal toxicities of various organophosphate insecticides in mice

Abstract: Dermal LD50 values for five organophosphate insecticides were determined in mice by application of solutions to hind feet. Values were simultaneously generated for the ED50 (milligrams per kilogram) for both cholinesterase and acetylcholinesterase. Lethality was greatest with mevinphos, followed by parathion, methyl parathion, diazinon, and azinphosmethyl. LD50 values were higher than reported values for mice treated on shaved back skin. Cholinesterase ED50 values roughly agreed with LD50 values for mevinphos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Influences on the pharmacokinetics of methyl paraoxon and the activity of acetylcholinesterase follow in turn. Yet, there are only limited data related to methyl parathion with which to predict the potential long-term health risks resulting from a pattern of exposure that occurred with its use in domestic settings [2,7,8,14,16,20,22,36,40]. Also, methyl parathion and other organophosphorus insecticides exhibit a broad range of toxicities and abilities to inhibit acetylcholinesterase [10,11,18,19], making inferences between agents and across species speculative at best.…”
mentioning
confidence: 99%
“…Influences on the pharmacokinetics of methyl paraoxon and the activity of acetylcholinesterase follow in turn. Yet, there are only limited data related to methyl parathion with which to predict the potential long-term health risks resulting from a pattern of exposure that occurred with its use in domestic settings [2,7,8,14,16,20,22,36,40]. Also, methyl parathion and other organophosphorus insecticides exhibit a broad range of toxicities and abilities to inhibit acetylcholinesterase [10,11,18,19], making inferences between agents and across species speculative at best.…”
mentioning
confidence: 99%
“…This is in agreement with Marinovich et al 44 that a mixture of diazinon, dimethoate and azinophos was more toxic to protein synthesis than any of the single compounds alone, whereas it was equal to a maximum toxic compound as relates to inhibition of AChE activity. Furthermore, the toxicity of diazinon compared with methyl parathion is related to the animal species, thus the dermal toxicity of methyl parathion was higher than diazinon in mice, 35 whereas in another study, diazinon was more toxic than methyl parathion in Anquilla anquilla. 45 Furthermore, exposure of rainbow trout fish to a mixture of diazinon and malathion significantly decreased cholinesterase activity and differed significantly among exposure durations, 46 whereas Cha et al 8 showed that pretreatment of mice with diazinon completely blocked the serum esterase activity and enhanced ethyl carbamate toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to the low level of plasma BuChE during pregnancy. 21 Skinner and Kilgore 35 reported that diazinon was much more inhibitory on blood than the nervous system tissue cholinesterase in mice. Also, exposure of Anquilla anquilla to diazinon inhibited plasma BuChE activity by >90% of control.…”
Section: Discussionmentioning
confidence: 98%
“…The LD 50 value for methyl parathion dissolved in xylene and applied to the backs of male and female rats was reported to be 67 mg/kg [Gaines 1960]. In another study, the LD 50 value for methyl parathion dissolved in acetone and applied to the hind foot of mice was 1200 mg/ kg [Skinner and Kilgore 1982a]. The reported acute dermal LD 50 value for methyl parathion in rats is lower than the critical dermal LD 50 value of 200 mg/kg that identifies chemical substances that are potentially fatal at relatively low doses following dermal exposure [NIOSH 2009].…”
Section: Overview Of Sk Assignmentmentioning
confidence: 97%